Taste disturbance after tonsillectomy: a rare but significant complication- a case report - Kabir, Misbah Al; Afsana, Sultana Dil (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Tonsillectomy is the most commonly performed procedure and generally regarded as a safe surgery. Taste disturbance is a very rare complication after tonsillectomy, with very few reports in the literature. The most possible cause of this rare complication is direct or indirect damage to the glossopharyngeal nerve or its lingual branch (LBGN). Aim: To report a very rare complication of the most commonly performed procedure i.e. tonsillectomy. Case Report: The case is a 32 years old lady who complained of taste disturbance following tonsillectomy that was performed for chronic tonsillitis. As treatment patient was given Trifluoparazine Hydrochloride a Phenothiazine derivatives and Vit B6 + Vit B12. Patient recovered after 4 months postoperatively. Conclusion: Tonsillectomy should be performed with minimal trauma to the tonsillar bed to avoid injury to the Glossopharyngeal nerve or its lingual branch (LBGN) and all patients should be informed of the risk of post-operative taste disturbance after tonsillectomy. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22935 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014